Implementation of Safety Management System to Improve Safety Performance of Construction Workers: Literature Review - Maghfirah, Suci; Zakwan, M. Hadin; Marpaung, Fadhlan Al Hafiz; Hasibuan, Abdurrozzaq (AMK : Abdi Masyarakat UIKA, 2025)
The construction industry, known as one of the industries with the highest risk of workplace accidents, emphasizes the importance of occupational safety and health (OSH).One of the best ways to improve safety performance on site is by implementing a Safety Management System (SMS).The focus of this research is to collect and analyze various relevant studies on safety management systems and safety performance in the construction sector.The systematic literature review (SLR) method is used to collect and analyze various relevant studies regarding the implementation of SMS in the context of construction projects and its impact on worker safety performance.The analysis results show that the systematic and planned implementation of SMS can improve worker safety performance.